PENDIDIKAN DI GONTOR: IMPLIKASI TERHADAP PEMBELAJARAN BAHASA ARAB: EDUCATION IN GONTOR: IMPLICATIONS FOR ARABIC LANGUAGE LEARNING - Abdul Rahman, Mohammad Syukri; Man, Saupi; Daoh, Muhammad; Hussin, Md Noor; Zainuddin, Azammuddin; Hasan, Yaakob; Ab Latif, Khairatul Akmar; Zulkefli, Zarith Sofea (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
Pondok Modern Darussalam Gontor (PMDG) merupakan institusi pendidikan Islam terkenal dengan sistem pembelajaran yang ketat dan berdisiplin tinggi. Antara fokus utama institusi ini ialah pembelajaran bahasa Arab yang digunakan sebagai bahasa pengantar dalam pelbagai subjek. Artikel ini membincangkan sistem pendidikan bahasa Arab di PMDG dari aspek pendekatan pembelajaran, disiplin harian, kaedah pengajaran, cabaran serta manfaat kepada pelajar. Melalui metodologi tersendiri, PMDG berjaya melahirkan pelajar yang fasih, berdikari dan berdisiplin. Aspek kepimpinan pelajar, interaksi sosial, dan penggunaan harian bahasa Arab turut menyumbang kepada kejayaan sistem ini. Kajian ini turut meneliti peranan guru dalam menerapkan kaedah pengajaran berkesan serta pentingnya suasana berbahasa Arab bagi meningkatkan penguasaan pelajar. Dapatan kajian ini memberi gambaran tentang keunikan sistem PMDG dan potensi untuk dijadikan model oleh institusi pendidikan Islam lain. Pondok Modern Darussalam Gontor (PMDG) is a well-known Islamic educational institution recognized for its strict and highly disciplined learning system. One of its main focuses is the teaching of Arabic, which is used as the medium of instruction in various subjects. This article discusses the Arabic language education system at PMDG in terms of teaching approaches, daily discipline, teaching methods, challenges, and benefits for students. Through its unique methodology, PMDG has successfully produced students who are fluent, independent, and disciplined. Elements such as student leadership, social interaction, and the daily use of Arabic also contribute significantly to the success of this system. The study also examines the role of teachers in applying effective teaching methods and highlights the importance of an Arabic-speaking environment in enhancing students’ language proficiency. The findings of this study provide insight into the uniqueness of PMDG’s educational system and its potential to serve as a model for other Islamic educational institutions.